THE IMPACT OF ECOLOGICAL LITERACY ON REDUCING RESPIRATORY DISEASES (International journal of medical sciences, 2025)
This article analyzes the critical impact of ecological literacy on the primary prevention and reduction of respiratory diseases. Poor air quality, driven by anthropogenic pollutants (PM2.5, O3, NOx), is a leading environmental risk factor for respiratory morbidity (e.g., asthma, COPD, acute respiratory infections). From a preventive medicine and hygiene perspective, technological and policy-based solutions for emission reduction are long-term strategies. However, an immediate and sustainable intervention is the enhancement of public ecological literacy. This refers to the public's understanding of environmental hazards, their direct impact on health, and the subsequent adoption of protective and mitigative behaviors. This paper, following the IMRAD structure, systematically reviews the mechanisms through which ecological literacy influences health outcomes. It presents data synthesizing the links between environmental knowledge, attitudes, and protective practices (KAP). The results indicate that ecological literacy empowers individuals and communities to reduce personal exposure (e.g., use of air quality indices, masks) and support systemic changes (e.g., clean air policies). The article concludes with extensive recommendations for integrating environmental health literacy into public health policy and educational curricula as a fundamental tool for respiratory disease prevention.